Description of Physical Environment and The Existence of Sarcoptes Scabiei in Nails Prisoners Skabies Patients in Block A Country Jail Surabaya - Priyani Ida Nurohmah (JURNAL KESEHATAN LINGKUNGAN, 2018)
Skabies is one of the most contagious skin diseases and is caused by the Sarcoptes scabiei mite. The aims of this study was to identify the description of the environment physical conditions and the existence of Sarcoptes scabiei on the fingernails of prisoners of the penitentiary. This study was an observational research with cross sectional approach. The population was 682 prisoners and 26 samples. This sampling was determined by using purposive sampling method to select the respondents who fulfill the inclusion criteria that have been determined. Data obtained by observation sheet then analyzed descriptively. The results showed that the physical conditions of the environment in prisons that have not fulfilled the health requirements are the clean water provision, the density of occupancy and lighting. Based on nail examination, there were 2 positive people found Sarcoptes scabiei. The conclusion from this study was the condition of the water supply, the density of the occupancy and lighting was still not meet of the health requirements. Based on nail examination, there were 2 positive people found Sarcoptes scabiei. Prisons were advised to provide counseling about the skabies proliferation diseases.